The lexA gene product represses its own promoter. - Brent, R (1980)
The products of the lexA and recA genes of Escherichia coli regulate the cellular response to DNA damage (the SOS response). Here we describe the cloning of the wild-type lexA gene and the identification of its 24,000-dalton protein product. We also describe construction, by recombination in vitro, of a phage that bears the lexA promoter fused to the lacZ gene. Experiments with this fusion phage and with multicopy plasmids that carry the lexA gene showed that the lexA gene product represses of its own promoter. This repression occurs even if the cell has no recA gene, showing that the lexA protein need not be complexed to the recA protein for activity. Moreover, the presence of multicopy plasmids that carry the lexA gene blocks expression of all SOS responses tested. This presumably results from two effects: (i) repression of the recA gene, the product of which is required to activate many of these responses; and (ii) direct repression of other functions involved in the SOS response.